Structure–Activity Relationships for Rates of Aromatic Amine Oxidation by Manganese Dioxide - Salter-Blanc, Alexandra J; Bylaska, Eric J; Lyon, Molly A; Ness, Stuart C; Tratnyek, Paul G (Environmental science & technology, 2016)
New energetic compounds are designed to minimize their potential environmental impacts, which includes their transformation and the fate and effects of their transformation products. The nitro groups of energetic compounds are readily reduced to amines, and the resulting aromatic amines are subject to oxidation and coupling reactions. Manganese dioxide (MnO2) is a common environmental oxidant and model system for kinetic studies of aromatic amine oxidation. In this study, a training set of new and previously reported kinetic data for the oxidation of model and energetic-derived aromatic amines was assembled and subjected to correlation analysis against descriptor variables that ranged from general purpose [Hammett σ constants (σ–), pK as of the amines, and energies of the highest occupied molecular orbital (E HOMO)] to specific for the likely rate-limiting step [one-electron oxidation potentials (E ox)]. The selection of calculated descriptors (pK a, E HOMO, and E ox) was based on validation with experimental data. All of the correlations gave satisfactory quantitative structure–activity relationships (QSARs), but they improved with the specificity of the descriptor. The scope of correlation analysis was extended beyond MnO2 to include literature data on aromatic amine oxidation by other environmentally relevant oxidants (ozone, chlorine dioxide, and phosphate and carbonate radicals) by correlating relative rate constants (normalized to 4-chloroaniline) to E HOMO (calculated with a modest level of theory).